Oil Topography: Weaving the World of Oil - Borsa, Tomas; Beer, Ruth (Imaginations)

(untitled) (York University, 2022)
Taking inspiration from Pendakis and Wilson’s (2012) call to “sight, cite, and site” oil, in this piece we consider how interventions in artistic material practice can offer up complementary, and at times entirely unique, modes of engaging with the materialities of oil and petro-media. Building on conversations of the past several years, we make particular reference to Oil Topography (2014), a hand-woven jacquard tapestry created and produced by Ruth Beer.